A successful remote patient monitoring program for diabetes - Sawyer, Katlyn; Saxon, David; Zane, Richard; Patel, Hemali; McDermott, Michael; Singh, Vatsala; Lawler, Helen M. (Frontiers in Endocrinology, 2025)
The prevalence of diabetes continues to rise in the United States along with a shortage of endocrinologists. One proposed solution to this challenge is to deliver more specialty health care services through remote patient monitoring (RPM). Here, we describe our initial experience with an RPM program for diabetes care at the University of Colorado. We enrolled 211 patients with primarily uncontrolled type 2 diabetes into the Diabetes Home and Remote Care Program (DHRCP). Remote care replaced traditional brick-and-mortar care while patients were enrolled. A certified diabetes care and education specialists (CDCES) contacted patients every 1-2 weeks to provide lifestyle coaching and assess medication compliance. With oversight from an endocrinologist, frequent medication adjustments were made by the CDCES. Analysis performed on 106 (50.2%) patients who met graduation criteria and had a hemoglobin A1c (HbA1c) completed upon program graduation showed an average decrease in HbA1c from 10.4% to 7.0% (p<0.001). Overall, our results demonstrate that RPM is an effective care model for improving glycemic control in patients with diabetes.